Desenvolvimento de fermentado alcoólico de yacon - Brandão, Camila Cheker (2013)
The yacon is considered a functional food, because of its content of soluble fiber, the fructooligosaccharides (FOS), however it has a short shelf life and low volume production, producing an alcoholic fermented as an alternative for these problems. Thus, the aim of the study was to develop the alcoholic beverage, monitoring chemical changes during the elaboration process and aging (one year). After that time the antioxidant potential, the methanol content and an sensory analysis were conducted. The roots of yacon underwent alcoholic fermentation and the broth was monitored (temperature, pH, total acidity and soluble solids content) during ten days of the first (fast) fermentation and (density, ash, total and volatile acidity, tannins and sugars), during ninety days of slow stage of fermentation. At the end of the slow fermentation, the total acidity was the only requirement that varied significantly (p <0.05), decreasing over three months . During a year of aging were monitored ash, total acidity, volatile acidity, free and total SO2, the reducing sugar, sucrose, phenolic compounds and fructooligosaccharides (FOS). The volatile and total acidity increased significantly (p <0.05), over time, but at the end still retained within the law. As for the sugars, including FOS, were consumed during this period, sugesting the ability of yeast to hydrolyze the soluble fiber. The free and total SO2 decreased significantly, showing its performance against oxidation product. At the end of aging, methanol content presented was within those permitted by law, a good antioxidant potential and considerable profile and sensory acceptance. Thus, there was able to produce a fermented alcoholic from yacon, within the standards of Brazilian law, thereby becoming an alternative to the consumption of the roots.